Contestations of Transgender Rights and/in the Strasbourg Court - Vleuten, Anna van der (2020)
Transgender rights are a highly contested issue, upsetting the ‘normal’ ordering of society. In Europe, transgender persons continue to suffer discrimination and harassment, and their rights are contested time and again. Eventually they can turn to the European Court of Human Rights (the Court) in Strasbourg. In such politically sensitive matters, how do judges in Strasbourg decide? Do they set European norms bolstering transgender rights, or do they refrain from interference in state affairs? Testing expectations based on rational and sociological institutionalism, this article analyses all 33 Court cases on transgender issues since 1980. As a judge’s low score on trans rights in their home country does not mean that they vote against trans rights, and as judges do no defend their home country but vote with the ‘pro-state’ or ‘pro-trans’ majority, rationalist expectations were not confirmed. Sociological institutionalist processes of widening and narrowing tell us more about the hesitant and uneven strengthening of transgender rights, if within the limits of binary thinking as regards the transgender body, marriage and family.